Implementation of Effective Needs Assessment Learning Model Literacy in Klaogin Sorong Selatan Preparation Primary School - Ida Siti Hamidah (Syntax Idea)
Learning training using the needs assessment model approach carried out in Klaogin preparatory elementary schools is an effective way to reduce students' literacy disabilities. The aim of this research is to analyze the reasons why students are still unable to read and write. And help students in learning by using the needs assessment model method, so that the results obtained are more effective in a short time. The author, who is also an educator, found success in implementing this approach program which was carried out in one month of learning. Students get a 60% increase in results after being trained in literacy intensively.